Sustainability Planning Framework for Reducing Ground-level Ozone Formation in Construction Activities - Lewis, Phil; Shan, Yongwei; Hazzard, Elizabeth (Procedia engineering, 2015)
Many metropolitan areas struggle to meet the EPA standard for ozone. These areas need to realistically assess all potential pollutant emitting sources to comply. One pollution source that needs close examination is construction activities that employ nonroad diesel equipment that emit ozone-forming pollutants, including nitrogen oxides and volatile organic compounds. Furthermore, days exceeding the ozone standard typically occur between May and September, the same time of year when construction activity is at its peak; thus, a sustainable construction planning framework is needed to minimize conflicts between high pollutant emissions activities and forecasted high ozone days. This paper presents a framework for leveraging schedule float and allocating equipment resources for activities that may have the greatest impact on the formation of ground-level ozone. This scheduling approach will sustain good air quality by reducing ozone-forming emissions from construction activities.